PROBLEMATIC HADITHS IN QURRAH AL-ASHFIYA’ BY KIAI ZAINULLAH MALANG: An Intertextual Analysis - Hilal, Muhammad (RIWAYAH, 2024)
Qurrah al-Ashfiya’ ‘ala Syarh Nazhm Hidayah al-Adzkiya’ is a manuscript on Sufism written by Kiai Zainullah Malang. The book contains 74 hadiths and, after takhrij was carried out, three of them were found to have no original source in hadith compilation. This research aims to analyze these “problematic hadiths” using intertextual analysis developed by Julia Kristeva. Thus, this research is a hadith research with a multidisciplinary approach. The design used here is library research with a qualitative approach. The analysis technique used here is content analysis. This research finds that there are three problematic hadiths in Qurrah al-Ashfiya’. Through intertextual analysis, it is found that the first hadith is proven to be typographical error and subsequently disqualified as a hadith. The second one is narration bi al-ma‘na. The third one was found to have been inaccurately transcribed by Kiai Zainullah. Furthermore, it is proven that intertextual analysis can be an effective tool for resolving the limitations of takhrij al-hadits. The implication is that since intertextual analysis assumes that a text is always born in a network of multitext, all hadith basically have a source whose origins can be traced. Intertextual analysis does not recognize the term la ashl lahu (no chain of transmission is found).[Kitab Qurrah al-Ashfiyā’ ‘alā Syarh Nazhm Hidāyah al-Adzkiyā’ adalah sebuah manuskrip kitab tentang tasawuf yang ditulis oleh Kiai Zainullah dari Kabupaten Malang. Kitab ini berisi 74 hadis dan, setelah dilakukan takhrīj terhadapnya, tiga di antaranya tidak ditemukan dalam kitab-kitab himpunan hadis. Penelitian ini bertujuan menganalisis “hadis-hadis problematik” tersebut dengan menggunakan analisis intertekstual yang dikembangkan oleh Julia Kristeva. Penelitian ini adalah penelitian hadis dengan pendekatan multidisipliner. Desain penelitian yang digunakan adalah penelitian kepustakaan dengan pendekatan kualitatif. Teknik analisis yang digunakan adalah Analisis Isi. Penelitian ini menemukan bahwa terdapat tiga buah hadis problematik dalam kitab Qurrah al-Ashfiyā’. Melalui analisis intertekstual, didapati bahwa hadis pertama mengalami kekeliruan tipografis dan akibatnya tidak tergolong sebagai sebuah hadis. Hadis kedua adalah riwayat bi al-ma‘nā. Hadis ketiga didapati sebagai tertulis secara tidak akurat oleh Kiai Zainullah. Lebih dari itu, penelitian ini membuktikan bahwa analisis intertekstual bisa menjadi alat efektif untuk menyelesaikan batasan-batasan yang dimiliki oleh takhrīj al-ḥadīth. Implikasinya, oleh karena analisis intertekstual berasumsi bahwa sebuah teks senantiasa lahir dalam sebuah jaringan multiteks, maka semua hadis pada dasarnya punya sumber yang asal-usulnya bisa dilacak. Analisis intertekstual tidak mengakui terma lā ashl lahu (sanadnya tidak ditemukan).]